Evaluating the impact of regulatory action on denosumab‐induced hypocalcaemia in Japan. (7th July 2019) - Imatoh, Takuya; Sai, Kimie; Takeyama, Mayu; Segawa, Katsunori; Yamashita, Takanori; Nakashima, Naoki; Kataoka, Yoko; Yokoi, Hideto; Hiramatsu, Tatsuo; Ohe, Kazuhiko; Kimura, Michio; Hori, Katsuhito; et al.
Abstract: What is known and Objective: Since its introduction in April 2012, denosumab has been administered to approximately 7, 300 patients as of August 2012, and 32 cases of serious hypocalcaemia after denosumab administration, including two deaths, have been reported in Japan. A Dear Healthcare Professional Letter of Rapid Safety Communication ('Blue letter') was released to warn about the risks of hypocalcaemia associated with denosumab. The goal of this study therefore was to measure the impact of regulatory action on denosumab‐induced hypocalcaemia in Japan by using an electronic medical information database (MID). Methods: We used two different aggregated data sets based on MIDs (data sets one and two). The patients studied were those who were newly prescribed denosumab or zoledronic acid between April 2012 and September 2014. We assessed four indicators: (a) the proportion of patients with calcium supplementation at the initial denosumab treatment, (b) the proportion of patients who underwent a serum calcium test, (c) the average number of serum calcium tests performed and (d) the prevalence of hypocalcaemia. All indices were aggregated by every 3 months. To evaluate the impact of regulatory action, we used difference in difference (DID) analysis. Results and Discussion: The proportion of patients with calcium supplementation at the initial denosumab treatment increased year by year in both data sets. The average number of serum calcium tests increased year by year in data set two. There was a significant difference in the prevalence of hypocalcaemia in data set two. This suggests that the estimate of impact of the regulatory action may vary according to the database. In DID analysis, however, significant influences of the regulatory action on combination use with a calcium supplement were detected in both data sets. What is New and Conclusion: There was a significant influence on combination use of denosumab with vitamin D and/or calcium supplement in both data sets. That there was no apparent increase in the prevalence of denosumab‐induced hypocalcaemia, suggests that the regulatory action had an impact in the clinical setting studied. Such regulatory actions may play an important role in the promotion of drug safety. Abstract : A Dear Healthcare Professional Letter of Rapid Safety Communication ('Blue letter') was released to warn about the risks of hypocalcemia associated with denosumab in Japan on June 2012. To assess the impact of the regulatory action, we assessed four indicators: (a) the proportion of patients with calcium supplementation at the initial denosumab treatment, (b) the proportion of patients who underwent a serum calcium test, (c) the average number of serum calcium tests performed, and (d) the prevalence of hypocalcemia. There was significant influence on combination use with vitamin D and/ or calcium supplement.